2024
DOI: 10.1371/journal.pone.0306771
|View full text |Cite
|
Sign up to set email alerts
|

High STI burden among a cohort of adolescents aged 12–19 years in a youth-friendly clinic in South Africa

Matt A. Price,
Monica Kuteesa,
Matthew Oladimeji
et al.

Abstract: Adolescents face a higher risk for HIV, STIs, and unintended pregnancy than any other age group in sub–Saharan Africa, and have unique health care needs as they navigate this period of growth and developmental milestones. We conducted the Youth Friendly Services study among adolescents in Rustenburg, South Africa to address some of these concerns. Participants aged 12–19 were followed quarterly for 12 months, asked at baseline about demographics, their sexual behavior, and tested for HIV, STIs, and pregnancy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The main parent study has been previously reported (23), where we recruited males and females aged between 12 to 19 years, who were HIV-negative and in females not pregnant.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The main parent study has been previously reported (23), where we recruited males and females aged between 12 to 19 years, who were HIV-negative and in females not pregnant.…”
Section: Study Design and Settingmentioning
confidence: 99%